Analysis Choices Impact Movement Evaluation: A Multi-Aspect Inferential Method Applied to Kinematic Curves of Vertical Hops in Knee-Injured and Asymptomatic Persons - Strandberg, Johan; Pini, Alessia; Häger, Charlotte K.; Schelin, Lina (Frontiers in Bioengineering and Biotechnology, 2021)
Three-dimensional human motion analysis provides in-depth understanding to optimize sports performance or rehabilitation following disease or injury. Despite well-established methods, different analysis choices may influence the interpretation of the often complex biomechanical data. We evaluated the consequences of such choices when comparing one-leg vertical hop performance in individuals who had ruptured their anterior cruciate ligament (ACL), to that of asymptomatic controls, and also athletes. Kinematic data were analyzed using a novel statistical approach for curve data. This was done not only for one joint at a time but also for multiple lower limb joints and movement planes simultaneously using a multi-aspect methodology, testing for group differences while also accounting for covariates. We present the results of when an individual representative curve was either: 1) a mean curve (Mean), 2) a curve from the highest hop (Max), or 3) a curve describing the variability (Var), as a representation of performance stability. We also evaluated choice of sample leg comparisons; e.g., ACL-injured leg compared to either the dominant or non-dominant leg of asymptomatic groups. Finally, we explored potential outcome effects for different combinations of included joints. There were slightly more pronounced group differences when using Mean compared to Max, while the specifics of the observed differences depended on the outcome variable. For Var there were less significant group differences. Generally, there were more disparities throughout the hop movement when comparing the injured leg to the dominant leg of controls, resulting in e.g., group differences for trunk and ankle kinematics, for both Mean and Max. When the injured leg was instead compared to the non-dominant leg of controls, there were trunk, hip and knee joint differences. For a more stringent comparison, we suggest considering to compare the injured leg to the non-dominant leg. Finally, the multiple-joint analyses were coherent with the single-joint analyses. The direct effects of analysis choices can be explored interactively by the reader in the supplementary material. The choices definitively impact the interpretation of a hop test commonly used in rehabilitation following knee injuries. We recommend well-reasoned choices based on clear pre-rationales, and consensus of best-practice in the specific field.